Autonomic Management of Mobile Multimedia Services 9th IFIP/IEEE International Conference on Management of Multimedia and Mobile Networks and Services, MMNS 2006, Dublin, Ireland, October 25-27, 2006, Proceedings - Helmy, Ahmed; Jennings, Brendan; Murphy, LIam; Pfeifer, Tom (Computer Communication Networks and Telecommunications, 2006)
th This volume presents the proceedings of the 9 IFIP/IEEE International Conference on Management of Multimedia and Mobile Networks and Services (MMNS 2006), th th which was held from October 25 to 27 as part of Manweek 2006 in Dublin,Ireland. In line with its reputation as one of the pre-eminent fora for the discussion anddebate of advances in management of multimedia networks and services, the 2006 iteration of MMNS brought together an international audience of researchers and practitioners from both industry and academia. One of the most signi?cant trends of recent years has been the development and considerable market penetration of multimedia-capable mobile handsets. Nevertheless, signi?cant research challenges remain in the area of management of mobile networks supporting multimedia services; challenges which must be addressed by the research community if the vision of ubiquitous availability of advanced multimedia services is to be realised. The MMNS Steering Committee, noting the growing interest within the research community on solving issues relating speci?cally to the transport of multimedia traf?c over various mobile access technologies, made the signi?cant decision to change the long name of the MMNS conference to re?ect this change in focus. For2006 and subsequent years, it will be called "Management of Multimedia and Mobile Networks and Services".